Culturas anuais e de cobertura no manejo de plantas daninhas em sistemas de produção de grãos - Silva, Ivan David Ferreira (2021)
In the cultivation of grains such as soybeans, weeds can cause productivity losses due to competition from natural resources and even difficulty in harvesting grains. The no-tillage system can provide the agroecosystem with the suppression of weeds by the phytomass layer that covers the soil, in addition to being associated with nutrient cycling, water use efficiency, among others. The objective of this work was to identify annual and cover crops that promote weed suppression and increase in grain yield in soybean production systems under no-tillage in the consolidation phase. The experiment was installed at the Federal University of Mato Grosso, Rondonópolis university campus. For this work, the harvests of 2017/2018, 2018/19, 2019/2020 and 2020/21 were analyzed. The soil in the area is classified as Oxisol. The reserarch was conducted in a randomized block design, with nine production systems sown in the off-season, and with four replications each, totaling 36 experimental plots. The treatments were, MC1: Fallow + no-tillage (PD); MC2: Fallow + conventional preparation (PC); CS1: C. spectabilis; CS2: P. glaucum; CS3: U. ruziziensis; CS4: C. cajan; IC1: Corn+C. spectabilis; IC2: Corn+U. ruziziensis. MIX: Mix: P. glaucum + C. spectabilis + C. cajan + U. ruziziensis; IC2: Corn+U. ruziziensis. The analyzed variables were phytomass of cover crops (kg ha-1 ), soil cover rate (%), weed population (plants/m²), dry phytomass of weeds (kg ha-1 ), control of weed infestation. weeds (%), weed infestation (%) and soybean yield (kg ha-1 ).All were implemented after the soybean harvest, consisting of fallow, annual and cover crops (single and intercropping). The results demonstrate that the use of annual and cover crops in off-season is an efficient tool in the integrated management of weeds. Treatments CS2, CS3 and MIX showed potential to reduce infestation and development of invasive species during the off-season, in addition to significant increases in soybean grain yield sown in succession.